2003
DOI: 10.1016/s0040-4039(03)00420-9
|View full text |Cite
|
Sign up to set email alerts
|

A concise and stereoselective synthesis of (+/−)-erythro-methylphenidate

Abstract: Abstract-A concise and stereoselective synthesis of racemic erythro-methylphenidate (1) is described. The coupling reaction between piperidine-2-thione (3) and 2-bromo-2-phenylmethylacetate (4) afforded the b-enaminocarbonyl compound 2 in 60% yield by a modified Eschenmoser sulfide contraction reaction. In most cases the bicyclic thiazolidinone 5 was produced. Diastereoselective reduction of 2 in the presence of borohydrydes furnished the (+/−)-erythro-methylphenidate in good yields with dr >95%. © 2003 Elsevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…It has been reported [26] that the coupling between piperidine-2-thione and 2-bromo-2-phenylmethylacetate afforded the β-enaminocarbonyl in around 60% yield by using Eschenmoser sulfide contraction reaction and in most cases the bicyclic thiazolidinone was produced (4%-41%). [26] However, the possibility of by-product formation is very likely, as described before by Eschenemoser et al, [27] Neto [5,28] and others.…”
Section: N-substitutedmentioning
confidence: 99%
“…It has been reported [26] that the coupling between piperidine-2-thione and 2-bromo-2-phenylmethylacetate afforded the β-enaminocarbonyl in around 60% yield by using Eschenmoser sulfide contraction reaction and in most cases the bicyclic thiazolidinone was produced (4%-41%). [26] However, the possibility of by-product formation is very likely, as described before by Eschenemoser et al, [27] Neto [5,28] and others.…”
Section: N-substitutedmentioning
confidence: 99%
“…Various methods and approaches, such as classical resolution [19,[21][22][23][24] use of enantiomerically pure precursors and enantioselective synthesis approaches, and as well as others, to the preparation of enantiomerically pure (2R,2′R)-(+)-threo-methylphenidate are proposed [26][27][28][29][30]. Resolution via enzymatic hydrolysis, which afford (2S,2′S)-(-)-threo and (2R,2′R)-(+)threo methylphenidate, is also described [31] and all have been reviewed [32].…”
Section: Methylphenidate-ritalin (Concerta An Extended-release Form mentioning
confidence: 99%
“…Published work has revealed that β-enamino esters can easily be reduced into the corresponding β-amino esters. [50][51][52][53] A few methods for the reduction of piperidinic β-enamino esters have been described, [38,[47][48][49] but the free primary amines could not be isolated from the corresponding piperidinic β-amino esters or nitriles in any of the cases. As shown in Scheme 2, the intermediate 3 was successfully reduced to the key compound 4 after treatment with NaBH 3 CN in acidic conditions (HCl or acetic acid) and EtOH at 50°C, affording in good yield a crude mixture of inseparable diastereoisomers.…”
Section: Carbamate Seriesmentioning
confidence: 99%